Acidophilic algae isolated from mine-impacted environments and their roles in sustaining heterotrophic acidophiles - Johnson, David B. (Frontiers in Microbiology, 2012)
Two acidophilic algae, identified as strains of Chlorella protothecoides var. acidicola and Euglena mutabilis, were isolated in pure culture from abandoned copper mines in Spain and Wales and grown in pH- and temperature-controlled bioreactors. The Chlorella isolate grew optimally at pH 2.5 and 30 ˚C, with a corresponding culture doubling time of 9 hours. The isolates displayed similar tolerance (10-50 mM) to four transition metals tested. Growth of the algae in liquid media was paralleled with increasing concentrations of dissolved organic carbon (DOC). Glycolic acid was identified as a significant component (12- 14%) of total DOC. Protracted incubation resulted in concentrations of glycolic acid declining in both cases, and glycolic acid added to a culture of Chlorella incubated in the dark was taken up by the alga ( 100% within three days). Two monosaccharides were identified in cell-free liquors of each algal isolate: fructose and glucose (Chlorella), and mannitol and glucose (Euglena). These were rapidly metabolised by acidophilic heterotrophic bacteria (Acidiphilium and Acidobacterium spp.) though only fructose was utilised by the more fastidious heterotroph ”Acidocella aromatica”. The significance of algae in promoting the growth of iron- (and sulfate-) reducing heterotrophic acidophiles that are important in remediating mine-impacted waters is discussed.